Postpolypectomy Electrocoagulation Syndrome: A Mimicker of Colonic Perforation. (15th July 2013) - Benson, Brian C.; Myers, Jonathan J.; Laczek, Jeffrey T.
Abstract : Postpolypectomy electrocoagulation syndrome is a rare complication of polypectomy with electrocautery and is characterized by a transmural burn of the colon wall. Patients typically present within 12 hours after the procedure with symptoms mimicking colonic perforation. Presented is the case of a 56-year-old man who developed abdominal pain six hours after colonoscopy during which polypectomy was performed using snare cautery. CT imaging of the abdomen revealed circumferential thickening of the wall of the transverse colon without evidence of free air. The patient was treated conservatively as an outpatient and had resolution of his pain over the following four days. Recognition of the diagnosis and understanding of the treatment are important to avoid unnecessary exploratory laparotomy or hospitalization.